2021
DOI: 10.1101/2021.03.22.436414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysical properties governing septin assembly

Abstract: Septin filaments build structures such as rings, lattices and gauzes that serve as platforms for localizing signaling and organizing cell membranes. How cells control the geometry of septin assemblies in poorly understood. We show here that septins are isodesmic polymers, in contrast to cooperative polymerization exhibited by F-actin and microtubules. We constructed a physical model to analyze and interpret how septin assemblies change in the presence of regulators in yeast extracts. Notably filaments diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
(155 reference statements)
2
3
0
Order By: Relevance
“…The distribution of filament lengths for both Cdc11a- and Cdc11b-capped octamers at steady state could be approximated by a left truncated exponential function, consistent with isodesmic polymer growth models ( Fig. 3 D ; Romberg et al, 2001 ; Skillman et al, 2013 ; Woods et al, 2021 ). Interestingly, septin assembly on curved membranes has been shown to be a cooperative process, where membrane-bound septins drive the recruitment of septins from the solution onto the membrane ( Shi et al, 2022 ).…”
Section: Resultssupporting
confidence: 67%
“…The distribution of filament lengths for both Cdc11a- and Cdc11b-capped octamers at steady state could be approximated by a left truncated exponential function, consistent with isodesmic polymer growth models ( Fig. 3 D ; Romberg et al, 2001 ; Skillman et al, 2013 ; Woods et al, 2021 ). Interestingly, septin assembly on curved membranes has been shown to be a cooperative process, where membrane-bound septins drive the recruitment of septins from the solution onto the membrane ( Shi et al, 2022 ).…”
Section: Resultssupporting
confidence: 67%
“…We therefore reconstituted septin assembly with recombinant proteins and planar supported lipid bilayers (SLBs) (Figure 4C). The distribution of filament lengths for both Cdc11a and Cdc11b-capped octamers at steady state could be approximated by a single exponential function, consistent with isodesmic polymer growth models (Figure 4D) (Romberg, Simon and Erickson, 2001;Skillman et al, 2013;Woods et al, 2021). Fitting to a single exponential function also allowed us to calculate an average filament length despite the diffraction limit of the light microscope and for Cdc11a octamers was 0.72 µm (~23 octamers) and for Cdc11b octamers 0.52 µm (~16 octamers) (Figure 4D).…”
Section: Identity Of Terminal Subunit Changes the Biophysical Properties Of Septin Filamentssupporting
confidence: 67%
“…To study the assembly process of membrane-bound septins, we used confocal microscopy and measured time-dependent septin adsorption onto membrane-coated beads with assays that were developed and used in our earlier studies ( 9 , 41 ). One main difference between our current and past studies is that here, the adsorption is measured over time, whereas in previous studies, we reported only the adsorption at steady state.…”
Section: Resultsmentioning
confidence: 99%